Bacillus cereus: An Ally Against Drought in Popcorn Cultivation - Uéliton Alves de Oliveira; Antônio Teixeira do Amaral Junior; Samuel Henrique Kamphorst; Valter Jário de Lima; Fábio Lopes Olivares; Shahid Khan; Monique de Souza Santos; Jardel da Silva Figueiredo; Samuel Pereira da Silva; Flávia Nicácio Viana; Talles de Oliveira Santos; Gabriella Rodrigues Gonçalves; et al. (Microorganisms)
Despite the development of adapted popcorn cultivars such as UENF WS01, strategies such as bacterial inoculation are being explored to enhance plant resilience to abiotic stress. This study investigates the impact of drought stress on popcorn cultivation. Specifically, the aim was to identify the benefits of Bacillus cereus interaction with the drought-tolerant hybrid UENF WS01 for its morphophysiology and growth by comparing inoculated and non-inoculated plants under water-stressed (WS) and well-watered (WW) conditions. This evaluation was conducted using a randomized complete block design in a factorial arrangement. For WS with inoculation samples, there were significant increases in relative chlorophyll content, maximum fluorescence intensity, and agronomic water use efficiency. Chlorophyll content increased by an average of 50.39% for WS samples, compared to a modest increase of 2.40% for WW samples. Both leaf and stem biomass also significantly increased for WS relative to WW conditions. Overall, B. cereus inoculation mitigated the impact of water stress, significantly enhancing the expression of physiological and morphological traits, even when paired with a drought-tolerant hybrid.